(3JYde jG aJi aGdLgd YGQs - (3eLghds
(3ChdgG (B:s
(3JYde jG aJi aGdLgd YGQ (B,, (3hdG jQVi Hg EdG MeGQ (B,, (3Hg fdJ GdeYGdj aj GdMjGI (B,, (3Hg YRj hLGgj cd YeQj (B,, (3gh Gdabg GdPj Ld bOQG (B,, (3aLd HbOQg bOQj hPcQj (B...s
(3BNQgG (B:s
... (3dbO gJaJ aj LfM djd MeGeg Ydi aff hgfG hEfj dfGFe cPHJ hHjJ Gddg (B,, (3dh cfJ YGTbG deG SHbJfj HGdHcGA MeGe CRYe Cfj gGFe Ph UHGHI dRj(B... (3JeJ GdCHjGJs
(3JHUQI GdeDda (B:s
(3ojfSH dCHj GdQHjY eMeO Hf GddjK Gdabjg , (B((3cGf MjG bHd (B193 (3g`(B)s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdCOHs